Pre-clinical assessment of a water-in-fluorocarbon emulsion for the treatment of pulmonary vascular diseases. (1st January 2019) - Ferguson, Scott K.; Pak, David I.; Hopkins, Justin L.; Harral, Julie W.; Redinius, Katherine M.; Loomis, Zoe; Stenmark, Kurt R.; Borden, Mark A.; Schroeder, Thies; Irwin, David C.
Abstract: Hypoxic pulmonary vasoconstriction (HPV) is a well-characterized vascular response to low oxygen pressures and is involved in life-threatening conditions such as high-altitude pulmonary edema (HAPE) and pulmonary arterial hypertension (PAH). While the efficacy of oral therapies can be affected by drug metabolism, or dose-limiting systemic toxicity, inhaled treatment via pressured metered dose inhalers (pMDI) may be an effective, nontoxic, practical alternative. We hypothesized that a stable water-in-perfluorooctyl bromide (PFOB) emulsion that provides solubility in common pMDI propellants, engineered for intrapulmonary delivery of pulmonary vasodilators, reverses HPV during acute hypoxia (HX). Male Sprague Dawley rats received two 10-min bouts of HX (13% O2 ) with 20 min of room air and drug application between exposures. Treatment groups: intrapulmonary delivery (PUL) of (1) saline; (2) ambrisentan in saline (0.1 mg/kg); (3) empty emulsion; (4) emulsion encapsulating ambrisentan or sodium nitrite (NaNO2 ) (0.1 and 0.5 mg/kg each); and intravenous (5) ambrisentan (0.1 mg/kg) or (6) NaNO2 (0.5 mg/kg). Neither PUL of saline or empty emulsion, nor infusions of drugs prevented pulmonary artery pressure (PAP) elevation (32.6 ± 3.2, 31.5 ± 1.2, 29.3 ± 1.8, and 30.2 ± 2.5 mmHg, respectively). In contrast, PUL of aqueous ambrisentan and both drug emulsions reduced PAP by 20–30% during HX, compared to controls. IL6 expression in bronchoalveolar lavage fluid and whole lung 24 h post-PUL did not differ among cohorts. We demonstrate proof-of-concept for delivering pulmonary vasodilators via aerosolized water-in-PFOB emulsion. This concept opens a potentially feasible and effective route of treating pulmonary vascular pathologies via pMDI.